2023
DOI: 10.1021/acscatal.2c06406
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Role of Dimeric Species: On-Cycle Involvement, Improved Stability, and Control of Stereo-Specificity. A Case Study of Atom-Economic Catalytic Hydrothiolation

Abstract: A common assumption that dimeric metal complexes in many catalytic systems represent a resting state and are not directly involved in catalytic processes was revised in a combined experimental and theoretical study. On-cycle participation of dimeric metal complexes, rather than typically assumed off-cycle involvement, was revealed, and advantageous performance in terms of improved selectivity was observed. The conceptual rationalization for the participation of dimeric species in the catalytic cycle was develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 116 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…Methods for creating carbon-heteroatom bonds, including C-S bonds, are in high demand in modern organic chemistry. [1][2][3][4][5][6][7][8][9][10] Sulfur-containing compounds are widely used as catalysts, 11,12 reagents and synthetic intermediates, [13][14][15][16][17][18][19] as well as for the preparation of biologically active compounds 20 and functional materials. 21,22 One important class of organosulfur compounds are sulfones, especially vinyl sulfones (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods for creating carbon-heteroatom bonds, including C-S bonds, are in high demand in modern organic chemistry. [1][2][3][4][5][6][7][8][9][10] Sulfur-containing compounds are widely used as catalysts, 11,12 reagents and synthetic intermediates, [13][14][15][16][17][18][19] as well as for the preparation of biologically active compounds 20 and functional materials. 21,22 One important class of organosulfur compounds are sulfones, especially vinyl sulfones (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Methods for creating carbon–heteroatom bonds, including C–S bonds, are in high demand in modern organic chemistry. 1–10 Sulfur-containing compounds are widely used as catalysts, 11,12 reagents and synthetic intermediates, 13–19 as well as for the preparation of biologically active compounds 20 and functional materials. 21,22…”
Section: Introductionmentioning
confidence: 99%
“…However, the zero-valent intermediate (NHC)­Pd 0 (py) has not been isolated so far. Based on isotopic labeling, MS spectrometry, nuclear magnetic resonance (NMR), and FE-SEM analysis, Ananikov and colleagues reported the formation of Pd 0 nanoparticles in combination with (NHC) 2 Pd and referred to this mixture as “catalytic cocktail” . They concluded that the presence of strong bases induces the reduction of the PEPPSI precursor complex, with the formation of Pd 0 nanoparticles and O–NHC coupling with urea formation in case of oxygen-derived bases…”
mentioning
confidence: 99%
“… 10 Furthermore, Ananikov et al showed that the dissociation of the NHC does not compromise the activity of the catalyst and that the presence of ureas might even boost turnover. 8 , 9 Cyclic (alkyl)(amino) carbenes (CAACs) stabilize low-valent compounds and radicals due to their π-acidity. 11 Although not yet quantified, they are also expected to show a strong trans-effect.…”
mentioning
confidence: 99%